Sequences in the 5′ and 3′ R Elements of Human Immunodeficiency Virus Type 1 Critical for Efficient Reverse Transcription - Ohi, Yuki (American Society for Microbiology, 2000)
The genome of human immunodeficiency virus type 1 (HIV-1) contains two direct repeats (R) of 97 nucleotides at each end. These elements are of critical importance during the first-strand transfer of reverse transcription, during which the minus-strand strong-stop DNA (−sssDNA) is transferred from the 5′ end to the 3′ end of the genomic RNA. This transfer is critical for the synthesis of the full-length minus-strand cDNA. These repeats also contain a variety of other functional domains involved in many aspects of the viral life cycle. In this study, we have introduced a series of mutations into the 5′, the 3′, or both R sequences designed to avoid these other functional domains. Using a single-round infectivity assay, we determined the ability of these mutants to undergo the various steps of reverse transcription utilizing a semiquantitative PCR analysis. We find that mutations within the first 10 nucleotides of either the 5′ or the 3′ R sequence resulted in virions that were markedly defective for reverse transcription in infected cells. These mutations potentially introduce mismatches between the full-length −sssDNA and 3′ acceptor R. Even mutations that would create relatively small mismatches, as little as 3 bp, resulted in inefficient reverse transcription. In contrast, virions containing identically mutated R elements were not defective for reverse transcription or infectivity. Using an endogenous reverse transcription assay with disrupted virus, we show that virions harboring the 5′ or the 3′ R mutations were not intrinsically defective for DNA synthesis. Similarly sized mismatches slightly further downstream in either the 5′, the 3′, or both R sequences were not detrimental to continued reverse transcription in infected cells. These data are consistent with the idea that certain mismatches within 10 nucleotides downstream of the U3-R junction in HIV-1 cause defects in the stability of the cDNA before or during the first-strand transfer of reverse transcription leading to the rapid disappearance of the −sssDNA in infected cells. These data also suggest that the great majority of first-strand transfers in HIV-1 occur after the copying of virtually the entire 5′ R.